Early mobilisation versus plaster immobilisation of simple elbow dislocations: results of the FuncSiE multicentre randomised clinical trial. Issue 6 (14th July 2015) - Iordens, Gijs I T; Van Lieshout, Esther M M; Schep, Niels W L; De Haan, Jeroen; Tuinebreijer, Wim E; Eygendaal, Denise; Van Beeck, Ed; Patka, Peter; Verhofstad, Michael H J; Den Hartog, Dennis
Abstract : Background/aim: To compare outcome of early mobilisation and plaster immobilisation in patients with a simple elbow dislocation. We hypothesised that early mobilisation would result in earlier functional recovery. Methods: From August 2009 to September 2012, 100 adult patients with a simple elbow dislocation were enrolled in this multicentre randomised controlled trial. Patients were randomised to early mobilisation (n=48) or 3 weeks plaster immobilisation (n=52). Primary outcome measure was the Quick Disabilities of the Arm, Shoulder, and Hand ( Quick -DASH) score. Secondary outcomes were the Oxford Elbow Score, Mayo Elbow Performance Index, pain, range of motion, complications and activity resumption. Patients were followed for 1 year. Results: Quick -DASH scores at 1 year were 4.0 (95% CI 0.9 to 7.1) points in the early mobilisation group versus 4.2 (95% CI 1.2 to 7.2) in the plaster immobilisation group. At 6 weeks, early mobilised patients reported less disability ( Quick -DASH 12 (95% CI 9 to 15) points vs 19 (95% CI 16 to 22); p<0.05) and had a larger arc of flexion and extension (121° (95% CI 115° to 127°) vs 102° (95% CI 96° to 108°); p<0.05). Patients returned to work sooner after early mobilisation (10 vs 18 days; p=0.020). Complications occurred in 12 patients; this was unrelated to treatment. No recurrent dislocations occurred. Conclusions: Early active mobilisation is a safe and effective treatment for simple elbow dislocations. Patients recovered faster and returned to work earlier without increasing the complication rate. No evidence was found supporting treatment benefit at 1 year. Trial registration number: NTR 2025.